Infographics on risks associated with COVID-19 and the willingness to get the AstraZeneca vaccine: two randomized online experiments - Lisa Felgendreff; Regina Siegers; Leonie Otten; Cornelia Betsch (BMC, 2024)
Abstract Background Germans hesitated to get vaccinated with AstraZeneca in the COVID-19 pandemic after reports of blood clots. Methods In two preregistered online experiments with stratified randomization (Study 1 N = 824, Study 2: N = 1,056), we tested whether providing evidence-based benefit-risk information reduces the perceived risk of the AstraZeneca vaccine and the perceived probability of blood clots due to the AstraZeneca vaccine and increases the vaccination intention. In Study 1, participants saw no infographic (control) or one of two infographics (low vs. high exposure risk varied by the underlying incidence rates). Study 2 additionally varied the infographic design displaying the risk information (presented as table, circle icons, or manikin-like icons). Results The infographic decreased the risk perception of the vaccine compared to no infographic (Study 1: Cohens d = 0.31, 95% CI [0.14, 0.48]; Study 2: Cohens d = 0.34, 95% CI [0.06, 0.62]), but it did not influence the perceived probability of blood clots due to the AstraZeneca vaccine (Study 2: Cohens d = 0.05, 95% CI [-0.23, 0.33]). Also, the infographic design did not affect the perceived probability of blood clots (Study 2). The vaccination intention was not affected by viewing the infographic (Study 1: Cohens d = 0.04, 95% CI [-0.13, 0.21]; Study 2: Cohens d = 0.04, 95% CI [-0.24, 0.32]) nor the presented infection rate (Study 1: Cohens d = 0.07, 95% CI [-0.09, 0.24], Study 2: Cohens d = 0.01, 95% CI [-0.12, 0.15]) but by risk perceptions, sociodemographic characteristics, confidence in the AstraZeneca vaccine, and preference for alternative vaccines. Conclusions The evidence-based benefit-risk information helped putting the risk of vaccinations into perspective. Nevertheless, objective risk information alone did not affect vaccination intention that was low due to the preexisting lacking vaccine confidence.